The Situation for Influenza in the World in Summer 2015 and the Preliminary Forecast for the Upcoming Season 2015 - 2016 - O. L. Kiselev; L. S. Karpova; M. Yu. Pelih; A. Yu. Popova (Эпидемиология и вакцинопрофилактика)
The analysis of the spatial-temporal distribution of influenza data weekly to WHO data in the summer of 2015 in the countries of the Southern and Northern hemispheres It is shown that in the Southern hemisphere registered a moderate influenza epidemics in Oceania and South Africa and local and regional outbreaks. In the Northern hemisphere was registered to the local influenza outbreak and sporadic morbidity. The main causative agent of the influenza was virus influenza B, except Asia, where the predominant influenza A(H3N2). In the Northern hemisphere the proportion of influenza was greater, than in the South. Influenza A(H1N1)pdm09 were detected mainly in Africa and S. America. Antigenic analyses of influenza viruses revealed the circulation in Canada of strain B/Massachusetts/2/2012 (Yamagata line) (69.7%) and A/Switzerland/9715293/2013(H3N2) (8.6%), while in N. Zealand - B/ Phuket/3073/2013(Yamagata line) (45%) and strain A/Switzerland/9715293/2013(H3N2) (24.8%). Virus A(H1N1)pdm09 was represented by the strain A/California/7/2009 in both countries. In the epidemic season 2015 - 2016 will continue circulation previously identified influenza viruses, but we cannot exclude the possibility of emergence of new strains of influenza viruses. In Russia you can expect a mixed epidemic (A(H3N2), A(H1N1)pdm09 and B) moderate intensity at the usual time (in the second half of January).